Students' motivation towards science learning and students' science achievement - Chan, Ying Ling; Che Hassan, Norlizah (Human Resource Management Academic Research Society, 2017)
The aim of this study is to identify the level of students’ motivation towards science learning and students’ science achievement. This study also identifies gender differences and examine how the students’ motivation towards science learning relates with parental education level and students’ science achievement. There are 165 respondents involved who have been selected randomly from ten secondary schools in Pahang, Malaysia. A survey questionnaire was utilized in this study and the instrument employed was Students’ Motivation towards Science Learning (SMTSL). The result revealed that the students were moderately motivated towards science learning and achieved mid-low achievement in their science subjects. There was a significant difference in the mean of student’s motivation towards science learning scores for male students (M= 3.5418, SD= .44206) and female students [M= 3.7133, SD= .44106; t (163) = 2.361, p= .019]. The female students were significantly more motivated than male students in learning science. The result of the study indicated that students’ motivation towards science learning has a significant correlation with students’ science achievement (r =.354*, r²=.125, p=.000). Finally, recommendations are given to parents, teachers, policymakers and educational administrators, and serve as a means to improve students’ science achievement.